Duka Digital dan Kesehatan Mental pada Generasi Z dan Alpha: Tinjauan Literatur Sistematik - Farha, Ghitsna Nadila (Jurnal Konseling dan Psikologi Indonesia, 2025)
This study systematically reviews the interplay between digital grief and mental health outcomes in Generations Z and Alpha, focusing on publications from 2018 to 2025. A Systematic Literature Review (SLR) was conducted adhering to PRISMA guidelines. Searches on Google Scholar and Scopus using keywords such as “digital grief,” “online mourning,” and “mental health” yielded 412 articles, with 10 empirical studies meeting the inclusion criteria of topic relevance, clear adolescent or young adult samples (Gen Z and Alpha), quantitative or mixed-method approaches, and non-COVID-19 contexts. The synthesis reveals that digital platforms, including social media and online support groups, serve as both facilitators and inhibitors of grief processing. Online support groups and therapeutic interventions significantly reduce prolonged grief, depression, and anxiety, particularly for Gen Z, with effect sizes ranging from moderate to large (Cohen’s d=0.80–1.03). However, public expressions of grief on social media, such as memorial posts, can exacerbate distress and rumination, especially when perceived as performative. Key mediators include privacy concerns, social support availability, and digital literacy. The novelty of this review lies in its focus on Generations Z and Alpha, understudied cohorts in digital grief research, with studies spanning diverse contexts (e.g., Italy, Philippines, Sweden, USA). These findings underscore the dual role of digital platforms in shaping mental health outcomes and provide an empirical basis for tailored interventions, such as digital-focused cognitive behavioral therapy and privacy education, to support healthy grief processing in young populations.